APOE in the Normal Brain - Flowers, Sarah A. (Neurobiol Dis, 2020)
The APOE4 protein affects the primary neuropathological markers of Alzheimer’s disease (AD): amyloid plaques, neurofibrillary tangles, and gliosis. These interactions have been investigated to understand the strong effect of APOE genotype on risk of AD. However, APOE genotype has strong effects on processes in normal brains, in the absence of the hallmarks of AD. We propose that CNS APOE is involved in processes in the normal brains that in later years apply specifically to processes of AD pathogenesis. We review the differences of the APOE protein found in the CNS compared to the plasma, including post-translational modifications (glycosylation, lipidation, multimer formation), focusing on ways that the common APOE isoforms differ from each other. We also review structural and functional studies of young human brains and control APOE knock-in mouse brains. These approaches demonstrate the effects of APOE genotype on microscopic neuron structure, gross brain structure, and behavior, primarily related to the hippocampal areas. By focusing on the effects of APOE genotype on normal brain function, approaches can be pursued to identify biomarkers of APOE dysfunction, to promote normal functions of the APOE4 isoform, and to prevent the accumulation of the pathologic hallmarks of AD with aging.